CPIA Africa : Strengthening Debt Management Capacity - World Bank (World Bank, Washington, DC, 2019)
The 2019 Africa Country Policy and Institutional Assessment (CPIA) report covers the period January to December 2018. Over this period, the average quality of policies and institutions in International Development Association (IDA)-eligible countries remained unchanged, amid decelerating growth across the region. The overall CPIA score for IDA countries in Sub-Saharan Africa was 3.1 in 2018, the same as 2017, reflecting the slow progress in improving the quality of policy and institutional frameworks in the region.